Activated glycine receptors may decrease endosomal NADPH oxidase activity by opposing ClC-3-mediated efflux of chloride from endosomes. (February 2019) - McCarty, Mark F.; Iloki-Assanga, Simon; Lujan, Lidianys Maria Lewis; DiNicolantonio, James J.
Abstract: Receptor-mediated activation of NADPH oxidase complexes commonly occurs in endosomes; the hydrogen peroxide produced by the dismutation of superoxide generated within the endosomes often functions to boost receptor function by reversibly inhibiting protein tyrosine phosphatases or by promoting formation of signaling complexes. NADPH oxidase-mediated formation of superoxide entails transfer of two electrons (provided by NADPH) from the cytosol to the endosomal lumen, where two molecules of superoxide are generated. This charge transfer must be balanced if NADPH oxidase activity is to be sustained. In many cells, this balance is achieved by ClC-3, a chloride-proton antiporter which can extrude two chlorides from the endosome to balance the importation of two electrons. The efficiency of this chloride extrusion will evidently be contingent on the cytosolic chloride level. Pro-inflammatory hormones which stimulate NADPH oxidase activity in endosomes have been shown to promote chloride extrusion from the cell, thereby expediting endosomal chloride export. Conversely, high cytosolic chloride could potentially slow endosomal NADPH oxidase activity by impeding ClC-3-mediated chloride export. Glycine-activated, strychnine-inhibitable chloride channels, which boost intracellular chloride in cells which maintain intracellular chloride levels lower than that of plasma, have shown anti-inflammatory and anti-angiogenic activity in cell culture and rodent studies. It is proposed that many of these effects may be attributable to glycine-mediated suppression of endosomal NADPH oxidase activity. This model suggests that supplemental glycine may have utility for prevention and control of atherosclerosis, heart failure, angiogenesis associated with cancer or retinal disorders, and a range of inflammation-driven syndromes – including metabolic syndrome; and it might complement the suppression of NADPH oxidase activity achievable with phycocyanobilin-enriched spirulina extracts.